Do Management Interventions Last? : Evidence from an Experiment in India - Bloom, Nicholas; Mahajan, Aprajit; McKenzie, David; Roberts, John (World Bank, Washington, DC, 2018)
Between 2008 and 2010, the authors worked with a leading global consulting company to attempt to improve management in Indian textile firms. They conducted a randomized experiment involving 28 plants in 17 firms in the woven cotton fabric industry. These were large firms, with an average of 270 employees, and a median of two plants per firm. The authors interviewed the directors and plant managers about each of the 38 management practices to understand why practices were adopted or dropped over time. They find the treated firms to be using more looms and fewer workers over time, although neither is statistically significant. Finally, the results provide an illustration of the usefulness of returning to projects long after the intervention has ended.